Application of a Microseismic Method of Rock Burst Risk Assessment under Blasting Mining in Ashele Copper Mine. (21st February 2022) - Xu, Shida; Yang, Xinlu; Zhang, Feifei; Liu, Jiaqi
Abstract : Rock burst is a violent release of energy stored in the rock mass, which has been the focus of metal mine engineers. It gradually becomes a serious threat to both the mine's workers and equipment. Rock burst risk assessment is a key issue in the prevention of rock burst. Based on the microseismic method for rock burst risk assessment that is used in tunnels, this paper presents a method of rock burst risk assessment for metal mines combining a simplified probability function and principal component analysis (PCA). Specifically, the size and details of key monitoring area and risk assessment units are determined according to the distribution of the fracture and driving stress during deep mining process. Based on the correlation analysis, six microseismic parameters are selected to be used for rock burst risk assessment. Simple linear functions are temporarily used to construct probability functions of each parameter before enough rock burst cases are collected. The method has been successfully used in the deep mining section of the Ashele Copper Mine (approximately 1000 m deep). Additionally, among various microseismic indicators, the energy release rate and cumulative energy are the greatest contributors to rock burst of different intensities. Therefore, the proposed method in this paper provides an important reference for the prevention and control of rock burst in metal mines.